224k views
2 votes
Need help on this math problem!!!

Need help on this math problem!!!-example-1
User Mike Ryan
by
3.9k points

1 Answer

1 vote

Answer:


(fof^(-1))(x)=x

Explanation:

Composition of two functions f(x) and g(x) is represented by,

(fog)(x) = f[g(x)]

If a function is,

f(x) = (-6x - 8)² [where x ≤
-(8)/(6)]

Another function is the inverse of f(x),


f^(-1)(x)=-(√(x)+8)/(6)

Now composite function of these functions will be,


(fof^(-1))(x)=f[f^(-1)(x)]

=
[-6((√(x)+8)/(6))-8]^(2)

=
[-√(x)+8-8]^2

=
(-√(x))^2

= x

Therefore,
(fof^(-1))(x)=x

User Saurabh Chauhan
by
4.9k points